Early Enteral Nutrition Is Associated With Lower Mortality in Critically Ill Children. (May 2014) - Mikhailov, Theresa A.; Kuhn, Evelyn M.; Manzi, Jennifer; Christensen, Melissa; Collins, Maureen; Brown, Ann-Marie; Dechert, Ronald; Scanlon, Matthew C.; Wakeham, Martin K.; Goday, Praveen S.
Background : The purpose of this study was to examine the association of early enteral nutrition (EEN), defined as the provision of 25% of goal calories enterally over the first 48 hours of admission, with mortality and morbidity in critically ill children. Methods : We conducted a multicenter retrospective study of patients in 12 pediatric intensive care units (PICUs). We included patients aged 1 month to 18 years who had a PICU length of stay (LOS) of ≥96 hours for the years 2007–2008. We obtained patients' demographics, weight, Pediatric Index of Mortality–2 (PIM2) score, LOS, duration of mechanical ventilation (MV), mortality data, and nutrition intake data in the first 4 days after admission. Results : We identified 5105 patients (53.8% male; median age, 2.4 years). Mortality was 5.3%. EEN was achieved by 27.1% of patients. Children receiving EEN were less likely to die than those who did not (odds ratio, 0.51; 95% confidence interval, 0.34–0.76; P = .001 [adjusted for propensity score, PIM2 score, age, and center]). Comparing those who received EEN to those who did not, adjusted for PIM2 score, age, and center, LOS did not differ ( P = .59), and the duration of MV for those receiving EEN tended to be longer than for those who did not, but the difference was not significant ( P = .058). Conclusions : EEN is strongly associated with lower mortality in patients with PICU LOS of ≥96 hours. LOS and duration of MV are slightly longer in patients receiving EEN, but the differences are not statistically significant.